CATHINONES AND VIAGRA IN CHEMSEX: AN AUTOETHNOGRAPHY OF TOUCH, MASCULINITIES AND AESTHETICS - Jorge Humberto Lucero Díaz (Psicologia & Sociedade)
Abstract This article presents an autoethnographic analysis of chemsex, focusing on the simultaneous use of viagra and cathinones. The haptic and aesthetic dimensions of these encounters are examined, considering their effects on masculinities, gender, and sexual practices. A central tension emerges between haptic experimentation, which fosters a non-genital-centric sexuality, and the homonormative masculine aesthetics that shape these experiences. Adopting a multidisciplinary approach, the research is based on critically analyzed personal participation in chemsex, which was documented through field notes. The results reveal that chemsex practices are deeply relational, influenced by both pharmacological effects and aesthetic norms. The study concludes that chemsex constitutes a space of complex cultural transformation, where new forms of relationship, pleasure, and gender expression are challenged and redefined.